Transcriptomic analysis suggests a key role for SQUAMOSA PROMOTER BINDING PROTEIN LIKE, NAC and YUCCA genes in the heteroblastic development of the temperate rainforest tree Gevuina avellana (Proteaceae). Issue 2 (18th December 2015) - Ostria‐Gallardo, Enrique; Ranjan, Aashish; Chitwood, Daniel H.; Kumar, Ravi; Townsley, Brad T.; Ichihashi, Yasunori; Corcuera, Luis J.; Sinha, Neelima R.
Summary: Heteroblasty, the temporal development of the meristem, can produce diverse leaf shapes within a plant. Gevuina avellana, a tree from the South American temperate rainforest shows strong heteroblasty affecting leaf shape, transitioning from juvenile simple leaves to highly pinnate adult leaves. Light availability within the forest canopy also modulates its leaf size and complexity. Here we studied how the interaction between the light environment and the heteroblastic progression of leaves is coordinated in this species. We used RNA‐seq on the Illumina platform to compare the range of transcriptional responses in leaf primordia of G. avellana at different heteroblastic stages and growing under different light environments. We found a steady up‐regulation of SQUAMOSA PROMOTER BINDING PROTEIN LIKE ( SPL ), NAC, YUCCA and AGAMOUS‐LIKE genes associated with increases in age, leaf complexity, and light availability. In contrast, expression of TCP, TPR and KNOTTED1 homeobox genes showed a sustained down‐regulation. Additionally, genes involved in auxin synthesis/transport and jasmonate activity were differentially expressed, indicating an active regulation of processes controlled by these hormones. Our large‐scale transcriptional analysis of the leaf primordia of G. avellana sheds light on the integration of internal and external cues during heteroblastic development in this species.